1998
DOI: 10.1038/sj.bjp.0702016
|View full text |Cite
|
Sign up to set email alerts
|

Rilmenidine reveals differences in the pharmacological characteristics of prejunctional α2‐adrenoceptors in the guinea‐pig, rat and pig

Abstract: 1 The a 2A and a 2D -adrenoceptor subtypes are thought to be species homologs most easily di erentiated on the basis of the potency of antagonists. In the present study we have compared the e ect of rilmenidine with two other selective a 2 -adrenoceptor agonists, UK-14304 (5-bromo-6-[2-imidazolin-2-ylamino]-quinoxaline) and clonidine, against electrically-evoked contractions in ®ve isolated preparations from the rat, guinea-pig and pig, and, where possible, determined the receptor subtype involved. 2 UK-14034,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The observation that the pharmacological properties of rilmenidine, clonidine, and oxymetazoline at α 2A -adrenoceptors differ substantially between various species 3,5,14 in concert with the present molecular data suggests that the rabbit α 2Aadrenoceptor is no reliable predictive model for the action of ligands at the human α 2A -adrenoceptor. It is of interest to note that rilmenidine acts as an antagonist not only at human, but also at the pig α 2A -adrenoceptor, 14 and that the pig and human α 2A -adrenoceptor are structurally most similar among mammals in the amino acid sequence (TABLE 1). 5 Hence, the action of ligands at central α 2A -adrenoceptors in humans can be predicted most reliably from experiments performed in pig preparations.…”
Section: Implications For the Use Of The Rabbit A 2a -Adrenoceptor Asmentioning
confidence: 63%
“…The observation that the pharmacological properties of rilmenidine, clonidine, and oxymetazoline at α 2A -adrenoceptors differ substantially between various species 3,5,14 in concert with the present molecular data suggests that the rabbit α 2Aadrenoceptor is no reliable predictive model for the action of ligands at the human α 2A -adrenoceptor. It is of interest to note that rilmenidine acts as an antagonist not only at human, but also at the pig α 2A -adrenoceptor, 14 and that the pig and human α 2A -adrenoceptor are structurally most similar among mammals in the amino acid sequence (TABLE 1). 5 Hence, the action of ligands at central α 2A -adrenoceptors in humans can be predicted most reliably from experiments performed in pig preparations.…”
Section: Implications For the Use Of The Rabbit A 2a -Adrenoceptor Asmentioning
confidence: 63%
“…The receptor in rat vas deferens has a high receptor reserve and is responsive to even weak α 2 -adrenoceptors agonists. 30 Taken together, our findings indicate that neither lung nor brain methanolic CDS extracts have the potential to activate α 2 -adrenoceptors and cast doubts on one of the central tenants of research into CDS, namely that CDS represents an endogenous, noncatecholamine agonist for α 2 -adrenoceptors. 4,9,10 Thus, our observations on the rat vas deferens provide no support for the seminal findings by Diamant and Atlas 7 that brain CDS (approximately 8 units/mL) inhibited neurogenic contractions of the rat vas deferens through a phentolamine-and yohimbine-sensitive (α 2 -adrenoceptor) mechanism.…”
Section: Discussionmentioning
confidence: 76%
“…The finding that the CDS extracts were inactive at prejunctional α 2 ‐adrenoceptors in the rat vas deferens makes it unlikely that it possesses agonist activity in other models of α 2 ‐adrenoceptors. The receptor in rat vas deferens has a high receptor reserve and is responsive to even weak α 2 ‐adrenoceptors agonists 30. Taken together, our findings indicate that neither lung nor brain methanolic CDS extracts have the potential to activate α 2 ‐adrenoceptors and cast doubts on one of the central tenants of research into CDS, namely that CDS represents an endogenous, noncatecholamine agonist for α 2 ‐adrenoceptors 4,9,10.…”
Section: Discussionmentioning
confidence: 78%
“…At a stimulation frequency of 6 Hz, at which the concentration of the endogenous norepinephrine in the synaptic cleft is much higher, leading to a more pronounced activation of the ␣ 2A -autoreceptors than at 2 Hz, rilmenidine enhanced evoked [ 3 H]norepinephrine release; in other words, it again exhibited the typical behavior of an antagonist at ␣ 2A -autoreceptors in that it disinhibited release. Interestingly, it has recently been reported that rilmenidine was also devoid of agonistic activity at the ␣ 2A -adrenoceptors in porcine tail artery and urinary bladder, 20 which are structurally most similar to the human ␣ 2A -adrenoceptors (Table 2).…”
Section: Different Pharmacological Properties Of Human and Rabbit ␣ 2mentioning
confidence: 99%